Voices of Those Who Bear the Brunt – Experiences of Programme Personnel Concerning Private Sector Tuberculosis Notifications in Bengaluru City, India. Issue 7 (17th November 2021) - Meundi, Anand D.; Erasmus, Vicki; Nagaraja, Sharath B.; Richardus, Jan Hendrik
ABSTRACT: This study aims to assess private and public sector contributions to Tuberculosis (TB) notification in Bengaluru city (2011 to 2016) and identify challenges of program personnel in their interaction with private practitioners and procedural barriers for TB notification from the private sector as perceived by them. A mixed methods study was carried out in Bengaluru city, India with TB notification data obtained from TB Units in addition to in-depth interviews with key program implementers. Results showed the contribution of private practitioners to TB notification to be about 20%. Barriers and challenges were: the private practitioners' hesitancy to refer the patients to public sector due to their fear of losing patients and dishonoring of diagnosis from private practitioners, lack of awareness about TB notification, lack of legal punitive measures and constant glitches on the notification website. These need to be resolved on priority to achieve the national target of TB elimination by 2025.